Dysregulation of Nitric Oxide Signaling in Microglia: Multiple Points of Functional Convergence in the Complex Pathophysiology of Alzheimer Disease - Stefano, George B; Esch, Tobias; Ptacek, Radek; Kream, Richard M (Medical science monitor, 2020)
Current critical thinking has displaced the elaborated beta amyloid theory as the underlying unitary mechanism of Alzheimer disease (AD) in favor of concerted, long-term disruption or dysregulation of broad-based physiological processes. We present a critical discussion in which a chronic state of systemic proinflammation sustained over the course of several decades and engendered by ongoing metabolic or autoimmune disease is predicted to promote severe disruptions of central neurological processes. Specifically, long-term functional rundown of microglial-mediated phagocytic activity in concert with aberrant expression and cellular deposition of beta amyloid and tau protein facilitates formation of senile plaques and neurofibrillary tangles. Within this functional context, we hypothesize that early initiation events in the pathophysiology of AD may operationally involve a convergence of dysregulated peripheral and central constitutive nitric oxide signaling pathways resulting from a chronic state of systemic proinflammation and leading to severely dysfunctional "hyperactivated" microglia.
Keywords: signální transdukce; Signal Transduction; oxid dusnatý; Humans; Nitric Oxide; lidé; Alzheimer Disease; Alzheimerova nemoc; Microglia; mikroglie